Penanganan Obstruksi Usus pada Anjing: Laporan Kasus - Erwin Erwin; Rusli Rusli; Amiruddin Amiruddin; Deni Noviana; Raden Roro Soesatyoratih; Arni Diana Fitri; Sitaria Fransiska Siallagan (Jurnal Veteriner, 2018)
Veterinary Hospital of Education Faculty of Veterinary Medicine, Bogor Agricultural University, received a Golden Retriever with clinical symptoms of anorexia, abdominal pain, vomiting and constipation in April 2016. Blood profile examination showed leukocytosis, erythropenia and low hemoglobin level. Radiographic examination without contrast showed a foreign body which is characterized by a large mass radiopaque in intestinal area. Forty-five minutes after the administration of radiographic contrast, contrast material was still in gastrium and only reached partial intestinal. Endoscopy examination showed there was irritation symptoms of the esophagus to gastrium. Black colored liquid was seen while the endoscope inserted into the gastric. Enterotomy was carried out to remove foreign objects. The foreign body is consisted of bones fragments and the plastic that was eaten by the patient. One week after surgery, the animals showed clinical symptoms and had a good appetite. These case can be prevented by not giving foods that contain animal bones and keeping animals in a dirty environment.